Effect of Floor Feeding Creep Feed on the Growth Performance and Mortality of Pigs After Weaning - Madie R. Wensley; Mike D. Tokach; Robert D. Goodband; Jordan T. Gebhardt; Jason C. Woodworth; Joel M DeRouchey; Matt Allerson; Mariana Menegat; Andy Boeschert (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 264 litters (PIC × Duroc (n = 180) or Choice Genetics × Duroc (n = 84)) corresponding to 2,497 nursery pigs were used in a 40-d trial (4-d pre-weaning and 36-d post-weaning) to determine the effect of floor feeding different pellet sizes of creep feed or lactation feed on the growth performance and mortality of pigs after weaning. Treatments were applied in the farrowing house for 4 d prior to weaning and consisted of a control (no creep feed), standard (1/8 in.) creep pellet, large (1/2 in.) creep pellet, or sow lactation feed. For each treatment, approximately 0.50 lb of creep feed per day, equally divided into 2 feedings (AM and PM) was provided on the mat in farrowing stalls. At weaning (approximately d 19 of age), pigs were transported to the nursery facility and randomized to pen within creep feeding treatment group. A total of 96 pens (48 feeders) were used, with one barrow pen and one gilt pen per feeder. Thus, feeder (2 pens) was the experimental unit. There were 26 pigs per pen (52 pigs per feeder) and 12 replications per creep feeding treatment. For creep feeding during lactation, floor feeding different pellet size creep feed or lactation feed had no effects on the percentage of piglets that consumed creep feed (eaters). For the first week post-weaning, pigs fed standard or large pellet creep feed had increased (P<0.001) ADG compared to pigs fed sow lactation feed or no creep feed. However, this was not driven by an improvement in ADFI. This resulted in an improved (P<0.001) F/G for pigs fed large pellet creep feed compared to pigs fed sow lactation feed or no creep feed, with pigs fed standard pellet creep feed intermediate. No differences in ADG, ADFI, or F/G were observed throughout the remainder of the nursery period. On a per pig placed basis, pigs fed large pellet creep feed had increased total BW gain (P= 0.024), ADG (P= 0.027), and improved F/G (P= 0.021) compared to pigs fed sow lactation feed, with the other two treatment groups intermediate. This response was a direct reflection of decreased (P= 0.050) total removal rate for pigs fed large pellet creep feed. In summary, floor feeding large pellet creep feed in lactation appears to improve nursery pig growth performance and fallout rates compared to creep feeding sow lactation feed, with standard pellet creep feed or no creep feed having an intermediate effect.
Keywords: creep feed; performance; pig; floor feeding; mortality; weaning